Implementation of an Inquiry Model Assisted with PHET and Teaching Aids to Improve Vocational Students' Learning Outcomes in The Sound Waves Concept - Mambai, Naomi Ernita; Triwiyono; Lumbu, Albert (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2022)
Physics learning still tends to be conventional and very rarely takes place using practicum media, so students become less enthusiast. This is contrary with students in vocational schools who tend to learn through practice. This study aims to determine the effect of guided inquiry model assisted with PhET media and teaching aids in physics learning outcomes of class X students of SMKN 3 Technology and Engineering Jayapura on the sound waves concept. This study used the pre-experimental method with one group pretest-posttest design, the research sample was selected from two (control and experimental class) of nine classes through a purposive sampling technique with 25 students each group. The study used pretest and posttest essay questions which were validated by experts. The pretest and posttest data were then tested for normality and the results were normal, then N-gain analysis and hypothesis testing α = 5% significance value were performed. The results of the N-gain analysis obtained were 0.70 where the average value of the posttest>pretest ranged from moderate to high for the experimental class while the N-gain was 0.57 where the average posttest>pretest ranged from low to moderate for the experimental of class control. The results of the hypothesis test were found (tcount < ttable) = (0,000 < 0,05) where H0 was rejected, so that there was an improvement in learning outcomes and there were differences in learning outcomes before and after learning with treatment in experimental class. The success of this treatment can be seen from the enthusiasm of the students who are involved independently in operating the PhET application on computer media and visual aids during learning. This learning pattern can be applied by readers/teachers in researchers but also in the development of teacher learning towards students' understanding of physics concepts.